The attitudes of parents toward the oral health of children and their reflection on the non-cavitated caries lesions. Issue 1 (April 2022) - Bağ, İrem
Abstract: Objective: To determine the extent of non-cavitated caries lesions in preschool children, and compare its relationship with socioeconomic status, oral and dental health practices, knowledge of caries prevention, and nutrition. Materials and methods: Ninety-seven parents of 36–72 month-old children completed a questionnaire on the socioeconomic status of the family, parent's knowledge of caries prevention, the children's oral health practices, and nutrition. In the children, the cavitated dental caries were assessed according to World Health Organization (WHO) criteria and non-cavitated caries lesions on occlusal and smooth surfaces were evaluated by Universal Visual Scoring System (UniViSS). Statistical analysis was conducted using the SPSS software program. The relationships between variables were assessed using the chi-square test and logistic (ordinal) regression analysis. Results: Statistically significant results were obtained relating to the parents' age, number of children, the time of first oral hygiene, frequency of tooth brushing, knowledge of caries prevention, drinks most often consumed by the children, and number of non-cavitated lesions. According to the regression model, the significant variables were caries activity (yes), drinks most often consumed by the children (milk–juice; juice–buttermilk), the frequency of tooth brushing (once a day, twice a day), observed changes in a child's teeth (change in color and breaks in teeth), the number of cavitated caries lesions and decayed, missing and filled teeth (dmft). Conclusions: The primary factors contributing to non-cavitated caries lesions include the time of first oral hygiene and frequency of tooth brushing. The early diagnosis of non-cavitated caries is essential for preventive measures.